Linezolid in Combination With Azoles Induced Synergistic Effects Against Candida albicans and Protected Galleria mellonella Against Experimental Candidiasis - Lu, Mengjiao; Yang, Xinmei; Yu, Cuixiang; Gong, Ying; Yuan, Lei; Hao, Lina; Sun, Shujuan (Frontiers in Microbiology, 2019)
The incidence of resistant Candida isolates has increased continuously in recent decades, especially Candida albicans. To overcome the resistance, the research on antifungal sensitizers has attracted considerable attention. Linezolid was found to inhibit the growth of Pythium insidiosum and synergize with amphotericin B against Cryptococcus neoformans. The objective of this study was to determine the interactions of linezolid and azoles against C. albicans in vitro and in vivo. In vitro, linezolid combined with azoles induced the synergistic effects not only against some susceptible C. albicans isolates but also against all tested resistant C. albicans isolates. For all resistant isolates, exposure to the combination of linezolid with azoles induced a significant decrease in the minimum inhibitory concentrations of azoles, from > 512 μg/mL to 0.5-1 μg/mL for fluconazole, from > 16 μg/mL to 0.25-1 μg/mL for itraconazole, and from > 16 μg/mL to 0.03-0.25 μg/mL for voriconazole. Additionally, linezolid synergized with fluconazole against biofilms that were preformed for ≤ 12 h from both susceptible and resistant C. albicans, and the sessile minimum inhibitory concentration of fluconazole decreased from > 1024 μg/mL to 1-4 μg/mL. In vivo, linezolid plus azoles prolonged the survival rate of infected Galleria mellonella larvae twofold compared with the azole monotherapy group; significantly decreased the fungal burden of the infected larvae; and reduced the damage of resistant C. albicans to the larval tissue. These findings will contribute to antifungal agent discovery and new approaches for the treatment of candidiasis caused by C. albicans.